2022
DOI: 10.3390/nu14030622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotic Supplementation on Exercise with Predominance of Aerobic Metabolism in Trained Population: A Systematic Review, Meta-Analysis and Meta-Regression

Abstract: The scientific literature about probiotic intake and its effect on sports performance is growing. Therefore, the main aim of this systematic review, meta-analysis and meta-regression was to review all information about the effects of probiotic supplementation on performance tests with predominance of aerobic metabolism in trained populations (athletes and/or Division I players and/or trained population: ≥8 h/week and/or ≥5 workouts/week). A structured search was performed in accordance with the Preferred Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…Santibañez-Gutierrez et al detailed the term big data (BD) primarily refers to the large volume of data and the processing technology that has accompanied it as network information technology has developed at such a rapid pace [29]. When big data is included in aerobics teaching at higher technical colleges, it will substantially impact the teaching of aerobics and the overall quality of physical education.…”
Section: Related Workmentioning
confidence: 99%
“…Santibañez-Gutierrez et al detailed the term big data (BD) primarily refers to the large volume of data and the processing technology that has accompanied it as network information technology has developed at such a rapid pace [29]. When big data is included in aerobics teaching at higher technical colleges, it will substantially impact the teaching of aerobics and the overall quality of physical education.…”
Section: Related Workmentioning
confidence: 99%
“…Clinical evidence suggests that exercise and probiotics impact gene expression through epigenetic mechanisms, resulting in heightened endogenous activity and subsequent changes in lipid metabolism 50,51 .HIIT has been known to emerge as a time-e cient and effective intervention for addressing metabolic dysfunction associated with menopause 52,53 by activating the AMP-activated protein kinase (AMPK) pathway and lipolysis 52 . Also, animal and human studies have demonstrated that exercise-induced activation of AMPK leads to decreased liver fat accumulation by suppressing de novo lipogenesis, enhancing fatty acid oxidation, and supporting mitochondrial function and integrity in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the crossover nature of our design, although challenging to execute, was extremely important for rigorous internal control and due to the known individualization and diversification that occurs in the gut microbiome and the associated endotoxin responses [ 9 , 47 ]. Our study’s focus on older endurance athletes over 39 years of age, which notably included female participants, addresses a critical gap in research, where females have traditionally been under-represented [ 48 ]. This inclusion is particularly significant given that older populations, including females, tend to exhibit higher rates of GI complications compared to their younger counterparts [ 15 ].…”
Section: Discussionmentioning
confidence: 99%